2013
DOI: 10.1111/jpc.12301
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of atherosclerosis in obese adolescents: Positive correlation of mean platelet volume and carotid intima media thickness

Abstract: MPV is significantly correlated with CCA thickness in obese adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
2
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 43 publications
1
6
2
2
Order By: Relevance
“…So, the level of MPV was low as atherosclerosis progressed in diabetes. Several studies showed that there is a strong positive correlation between MPV and FPG as well as HbA1c levels [9,[18][19][20], but it was in contrast to our research; we demonstrated that there was no association between MPVand HBA1c as well as FPG, but MPV was significantly associated with IMT, just like the conclusion of Arslan N et al [23]. IMT increases in the presence of diabetic macroangiopathy, which is thought to be a relatively easy, non-invasive technique to identify atherosclerosis.…”
Section: Discussioncontrasting
confidence: 85%
“…So, the level of MPV was low as atherosclerosis progressed in diabetes. Several studies showed that there is a strong positive correlation between MPV and FPG as well as HbA1c levels [9,[18][19][20], but it was in contrast to our research; we demonstrated that there was no association between MPVand HBA1c as well as FPG, but MPV was significantly associated with IMT, just like the conclusion of Arslan N et al [23]. IMT increases in the presence of diabetic macroangiopathy, which is thought to be a relatively easy, non-invasive technique to identify atherosclerosis.…”
Section: Discussioncontrasting
confidence: 85%
“…These mediators can contribute to inflammation and atherogenesis and may explain the association between MPV and atherosclerosis. It has been previously shown that larger platelets are associated with severity of CAD [31], PAD [32][33], and carotid atherosclerosis [34][35]. Possible mechanism for correlation of larger platelets with ischemic stroke as shown in our study may be the augmented rate of atherosclerosis unlike atrial fibrillation or other prothrombotic conditions.…”
Section: Discussioncontrasting
confidence: 39%
“…It has been demonstrated there is no relationship between MPV, platelet aggregation, carotid IMT, and the extent of coronary artery disease (23). However, a positive correlation between MPV and carotid IMT in obese adolescents was shown recently (24). Also, our study population consisted of patients who had non-atherosclerotic heart disease, and we found a positive correlation between thoracic aorta IMT and MPV.…”
Section: Discussionmentioning
confidence: 91%